The Influence of Islamic Service Quality, Product Quality, and Store Atmosphere on Purchase Decisions: The Mediating Role of Brand Image in Halal Café Consumers - Zahria, Indi (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2025)
This study examines the influence of Islamic service quality, product quality, and store atmosphere on purchase decisions, with brand image serving as a mediating variable. The research focuses on customers of Teras Angkringan Benkemebul, a halal café in Central Java, Indonesia. Employing a quantitative approach, data were collected from 96 respondents using purposive sampling. Structural equation modeling (SEM) was utilized to test the hypothesized relationships. The findings indicate that only product quality has a direct significant effect on purchase decisions. Store atmosphere significantly influences brand image, which in turn mediates the effects of both product quality and store atmosphere on purchase decisions. However, Islamic service quality shows no direct or mediated influence. This study contributes to the literature on consumer behavior in halal markets and offers strategic insights for brand positioning in small food and beverage enterprises.